Altering the development of the dopaminergic system through social play in rats: Implications for anxiety, depression, hyperactivity, and compulsivity. (24th August 2021) - Parvopassu, Anna; Oggiano, Maurizio; Festucci, Fabiana; Curcio, Giuseppe; Alleva, Enrico; Adriani, Walter
Highlights: Truncated-DAT rats are a model for hyperactivity and compulsivity. Adolescent WT rats grew with: WT peer, WT adult, or trunk-DAT one. WT rats that grew with a trunk-DAT show ADHD- and OCD-like behaviors. Anomalies of DA system can transfer onto developing rats, by anomalous play. Abstract: Dopamine is essential to many functions like reward, motivation, and attention; when its neural pathways do not function properly, various disorders (e.g., anxiety, depression, hyperactivity, compulsions) can arise. Truncated-DAT rats display persistent stereotypies and aggressiveness; hence they are a new valuable animal model to study the pathogenesis of these disorders. The focus of research is often on the individual epigenetic determinants and much less on the impact of social experiences. Here, we investigate the developmental impact of the social environment on adolescent wild type (WT) rats. We divided subjects at weaning into three groups: living with another adolescent (WT Peer), with a WT adult, or with a truncated-DAT one, and we observed homecage social behavior of these pairs (play, jump, victory, and "bullying") during whole adolescence. When adult, we observed the same subjects in plus maze, forced swim, and social preference tests to measure levels of anxiety, depression, and quality of social interactions. Compared to the other groups, WT rats that had spent their adolescence with a truncated-DAT adult as companion show more anxious, depressive, hyperactive, impulsive, and compulsive behaviours. Results confirm that social interactions and healthy play (i.e., when play has behavioural, social, and psychomotor rewards that support the cognitive, emotional and physical development of the individual) are essential to neurobehavioral maturation. Conversely, anomalous interactions like poor play and "bullying" in developing rats may impact onto their dopaminergic system. Consequently, an impoverished social play could be one of the factors contributing to the appearance of putative indexes of attention deficit hyperactivity disorder (ADHD) andobsessive–compulsive disorder (OCD).